Radio occultations - Melbourne, William G. (Wiley-Interscience, 2005)
This groundbreaking text provides: A comprehensive resource that clearly defines the latest topics and methodologies, Radio Occultations Using Earth Satellites is a must-have text for engineers, scientists, students, and managers in satellites communications, navigation, deep space and planetary exploration, aerospace, atmospheric science, physics, and engineering.